2018
DOI: 10.1371/journal.pone.0199289
|View full text |Cite
|
Sign up to set email alerts
|

Use of dietary and performance-enhancing supplements among male fitness center members in Riyadh: A cross-sectional study

Abstract: This study aimed to explore the health beliefs and patterns of dietary supplement usage among fitness center members. This cross-sectional study was conducted in four large indoor fitness centers in Riyadh, Saudi Arabia. This study involved male fitness center members aged ≥18 years with no speech or hearing disabilities. In-person interviews were conducted with fitness center members who agreed to participate using a newly developed questionnaire. Information on participants’ sociodemographics (e.g., age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…In a survey from Riyadh, the majority of young adult males used DS, and the most commonly consumed supplements were proteins (29%) [ 12 ]. Three other reports conducted among members of fitness centers in Riyadh showed that the prevalence of DS consumption was 37.8% [ 13 ], 44.5% [ 14 ], and 47.9% [ 15 ]. However, other reports from different cities in Saudi Arabia showed diverse proportions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey from Riyadh, the majority of young adult males used DS, and the most commonly consumed supplements were proteins (29%) [ 12 ]. Three other reports conducted among members of fitness centers in Riyadh showed that the prevalence of DS consumption was 37.8% [ 13 ], 44.5% [ 14 ], and 47.9% [ 15 ]. However, other reports from different cities in Saudi Arabia showed diverse proportions.…”
Section: Introductionmentioning
confidence: 99%
“…Whey protein can be rapidly digested and absorbed, and its specific amino acid composition aids in synthesizing muscle proteins [ 22 ]. Recent reports indicate that whey protein was the most commonly used dietary supplement among gymnasium users in Riyadh [ 13 , 14 , 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9] And according to a study by AlRuthia et al , 44.5% of participants were supplement users. [10] In an attempt to improve overall health,[11] nonetheless, consumers tend to not have enough knowledge about said supplements and its usage or if there is an interaction with other food substances, consumers tend to use them without consulting healthcare professionals. [1213] In 2008, in a study by Kennedy et al , most Americans in tandem of conventional medical treatment use vitamin supplements, but only about a third discuss their consumption with a physician.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest users are men and young people who use powdered protein supplements to increase muscle mass who get information from accredited nutritionists and consider themselves well informed and buy supplements online. AlRuthia et al 46 warn that public health campaigns are needed to educate the public about the potential harmful effects of DSEA if purchased from unofficial providers or ingested without consulting qualified professionals.…”
Section: Discussionmentioning
confidence: 99%